(untitled) (SCIENCE TIME JOURNAL, 2025)
This article explores visual perception verbs in English and Uzbek from a cognitive-linguistic perspective. Special attention is given to the semantic and grammatical characteristics of verbs such as to see, to look, ko‘rmoq, and qaramoq, which are classified using Y.V. Paducheva’s taxonomic approach (T-categories). The study also applies N.N. Boldyrev’s conceptual-taxonomic analysis, allowing for the identification of the hierarchical structure of the “visual perception” concept. The article outlines both obligatory and optional features of the concept, along with different levels and layers of the perception verb taxonomy. The comparative analysis reveals both similarities and differences in how visual perception verbs are expressed in English and Uzbek. The findings contribute to a deeper understanding of the relationship between linguistic units and cognitive structures.